(Un)Mind the gap: How organizational actors cope with an identity–strategy misalignment. (February 2020) - Wenzel, Matthias; Cornelissen, Joep P.; Koch, Jochen; Hartmann, Michael; Rauch, Madeleine
In this article, we explore how organizational actors cope with a perceived misalignment between their organization's identity and strategy. Based on an inductive, interpretive case study at a public broadcasting organization, we identify three cognitive tactics through which organizational members cope with an identity–strategy misalignment: contextualization, abstraction, and fatalism. Furthermore, we show that the enactment of these cognitive coping tactics coincides with specific strategy-related tasks that prioritize different aspects of an organization's identity and, therefore, invokes different conceptions of the identity–strategy misalignment. Based on these findings, we develop a framework that conceptualizes how organizational members cope with an identity–strategy misalignment. We end the article by discussing the implications of our study for further research on the linkages between organizational identity and strategy.